PELATIHAN MERANCANG LEMBAR KEGIATAN PESERTA DIDIK BERBASIS ELEKTRONIK (E-LKPD) MENGGUNAKAN GOOGLE SITES UNTUK PENDIDIK TINGKAT SMA/SMK - Sabandar, Vederico Pitsalitz; Palinussa, Anderson Leonardo; Makaruku, Yulian H; Tupamahu, Pieter Z (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service activity carried out aims to enhance the quality of educators, especially in facing the changes of the Society 5.0 era, so that educators can become more creative, plan engaging learning, and increase the interest and creativity of students in learning through training in designing electronic-based Teaching and Learning Materials (LKPD) using Google Sites. The training took place at SMA Negeri 1 SBB, Kecamatan Kairatu, Kabupaten West Seram District, and focused on educators at the high school and vocational school levels. The training activities used methods such as lectures, question and answer sessions, presentations, simulations, and tests, with 28 participants who were subsequently considered respondents. The instruments used included test questions presented in the form of questionnaires, aimed at assessing the participants' understanding of the training material. Based on the analysis of the participants' initial knowledge, an average score of 55.14% was obtained, categorized as low. In contrast, after the training, the analysis of the final understanding of the participants yielded an average score of 96.68%, categorized as high. Furthermore, based on the N-Gain test, an average score of 92.7% was obtained, indicating effectiveness. Based on these results, it can be concluded that the training materials provided have a significant impact on enhancing educators' understanding of the benefits of using technology in education